2021
DOI: 10.1002/batt.202100216
|View full text |Cite
|
Sign up to set email alerts
|

Chemo‐Mechanical Model of SEI Growth on Silicon Electrode Particles**

Abstract: Silicon anodes promise high energy densities of next-generation lithium-ion batteries, but suffer from shorter cycle life. The accelerated capacity fade stems from the repeated fracture and healing of the solid-electrolyte interphase (SEI) on the silicon surface. This interplay of chemical and mechanical effects in SEI on silicon electrodes causes a complex aging behavior. However, so far, no model mechanistically captures the interrelation between mechanical SEI deterioration and accelerated SEI growth. In th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(49 citation statements)
references
References 105 publications
2
47
0
Order By: Relevance
“…[92] Its continued reformation leads to linear-in-time capacity fade increasing with applied current. [83,94] Understanding and mitigating this effect is crucial for the development of high-energy silicon electrodes.…”
Section: Understanding the Sei From A Multi-scale And Multi-domain Ap...mentioning
confidence: 99%
“…[92] Its continued reformation leads to linear-in-time capacity fade increasing with applied current. [83,94] Understanding and mitigating this effect is crucial for the development of high-energy silicon electrodes.…”
Section: Understanding the Sei From A Multi-scale And Multi-domain Ap...mentioning
confidence: 99%
“…The concentration c 0 = c ref exp(ÀeU 0 /k B T) at the anode-SEI interface depends on the open circuit voltage (OCV) U 0 , which results from the state of charge SoC via the OCV-curve. 31,40,62 At this point, we summarize and non-dimensionalize the model equations. We use the characteristic time 1/(r 0 a 2 ) and the characteristic energy scale k B T. Table 1 lists the dimensionless parameters of our model.…”
Section: Theorymentioning
confidence: 99%
“…The concentration c 0 = c ref exp(− eU 0 / k B T ) at the anode-SEI interface depends on the open circuit voltage (OCV) U 0 , which results from the state of charge SoC via the OCV-curve. 31,40,62…”
Section: Theorymentioning
confidence: 99%
“…It was demonstrated that the composite Si can give higher cyclic stability as compared to bare Si as an anode material . The SEI formation on the anode surface protects the electrolyte from further decomposition and enhances the safety, cycle life, and performance. However, the initial capacity loss (ICL) of the Si anode is high due to the formation of surface film compounds on the anode surface during the first discharge process, and it is irreversible in nature. In addition, it also hinders the Li-ion transport, limiting the LIB’s capacity and dynamic reactivity, and the resistance across the layer restricts the current flow, resulting in a high ICL . The high ICL (∼60 to 65%) mainly restricts these high-capacity anodes in the full-cell fabrication and prevents their further commercial use. , …”
Section: Introductionmentioning
confidence: 99%